Does the diameter of the thoracic inlet influence the formation of retrosternal goiter? - Leonardo Daniel Manzano Pasquel; Daniel Abreu Rocha; Yasmin Laryssa Moura Guimaraes; Gustavo Fernandes de Alvarenga; Mauricio Kase; Júlia Scomparin Magalhãnes; Regina Lúcia Elia Gomes; Ledo Mazzei Massoni Neto; Renata Lorencetti Mahmoud; Leandro Luongo de Matos; Vergilius José Furtado de Araujo Filho; Claudio Roberto Cernea (Brazilian Journal of Otorhinolaryngology)
Objective: Find an association between diameter of the Thoracic Inlet (TI) and RSG to determine whether the TI would function as a natural anatomical barrier to prevent the passage of the goiters to the thoracic cavity. Methods: A retrospective study was conducted with patients submitted to total thyroidectomy, with goiter greater than 50 cm3, who underwent Computed Tomography (CT) preoperatively to measure the TI volume. The values obtained from each continuous variable of parametric distribution were organized and described as mean and standard deviation. The distributions were defined as non-parametric by the Kolmogorov-Smirnov test. The Mann-Whitney test was used to compare two sample populations. Results: A total of 173 patients submitted to total thyroidectomy were evaluated, and 54 patients met the inclusion criteria of the study. 85.2% were female, with a mean age of 57-years. The mean diameter of the TI was 5679 mm2. 42% of the patients presented some degree of RSG. The distance below the TI ranged from 0.2 to 5 cm. Conclusion: No significant association was found between diameter of the thoracic inlet and retrosternal goiter, demonstrating that RSG can be present regardless of the TI diameter. Statistically significant association was observed between patients with larger thyroid volume and the likelihood of this tissue to extend to the thoracic cavity. Level of evidence: Level IV.